STUDI DESKRIPTIF KOMPARASI TENTANG PSYCHOLOGICAL WELL-BEING PADA GENERASI SANDWICH DI KECAMATAN TOMOHON TENGAH KOTA TOMOHON - Reity Sengkey; Deetje J Solang; Marssel M. Sengkey (Program Studi Psikologi Universitas Negeri Manado, 2022)
This study aims to describe and compare the level of psychological well-being of the sandwich generation in the Tomohon Tengah sub-district, Tomohon City based on the categories in this study. The type of research used is descriptive quantitative research with a sample of 70 people of the sandwich generation, ages 21 to 60. The measuring instrument in this study uses Psychological Well-Being Scales (PWBS) developed by Ryff (1989) with 44 valid items and has a Cronbach Alpha reliability index of 0.885. The preparation of the item is based on aspects of psychological well-being, namely self-acceptance, positive relationships with others, environmental mastery, autonomy (independence), life goals and personal growth. The results of this study indicate that the level of psychological well-being in the sandwich generation is in the average category, there is no sandwich generation in the high or low category. Then when compared based on the criteria, the results show that there is no difference, so there is no striking level of psychological well-being because everything is equal.